Nuclear resonant scattering from (193)Ir as a probe of the electronic and magnetic properties of iridates - Alexeev, Pavel (Sci Rep, 2019)
The high brilliance of modern synchrotron radiation sources facilitates experiments with high-energy x-rays across a range of disciplines, including the study of the electronic and magnetic correlations using elastic and inelastic scattering techniques. Here we report on Nuclear Resonance Scattering at the 73 keV nuclear level in (193)Ir. The transitions between the hyperfine split levels show an untypically high E2/M1 multi-polarity mixing ratio combined with an increased sensitivity to certain changes in the hyperfine field direction compared to non-mixing transitions. The method opens a new way for probing local magnetic and electronic properties of correlated materials containing iridium and provides novel insights into anisotropic magnetism in iridates. In particular, unexpected out-of-plane components of magnetic hyperfine fields and non-zero electric field gradients in Sr(2)IrO(4) have been detected and attributed to the strong spin-orbit interaction in this iridate. Due to the high, 62% natural abundance of the (193)Ir isotope, no isotopic enrichment of the samples is required, qualifying the method for a broad range of applications.